Femoral versus Radial Access in Primary Angioplasty. Analysis of the ACCEPT Registry - Andrade,Pedro Beraldo de (2014)
Background:The radial access provides a lower risk of bleeding and vascular complications related to the puncture site in comparison to the femoral access. Recent studies have suggested a reduction in mortality associated with the radial access in patients with acute myocardial infarction undergoing percutaneous coronary intervention.Objective:To compare the occurrence of adverse cardiovascular ischemic and hemorrhagic events in patients undergoing primary angioplasty according to the type of arterial access route.Methods:From August 2010 to December 2011, 588 patients undergoing primary percutaneous coronary intervention during acute ST-segment elevation myocardial infarction were assessed; they were recruited from 47 centers participating in the ACCEPT registry. Patients were grouped and compared according to the arterial access used for the procedure.Results:The mean age was 61.8 years; 75% were males and 24% had diabetes mellitus. There was no difference between groups as regards the procedure success rate, as well as regards the occurrence of death, reinfarction, or stroke at six months of follow-up. Severe bleeding was reported in 1.1% of the sample analyzed, with no statistical difference related to the access used.Conclusions:The femoral and radial accesses are equally safe and effective for the performance of primary percutaneous coronary intervention. The low rate of cardiovascular events and of hemorrhagic complications reflects the quality of the participating centers and the operators expertise with the use of both techniques.